Beyond muscle hypertrophy: Why dietary protein is important for endurance athletes - Moore, D. R.; Camera, D. M.; Areta, J. L.; Hawley, J. A. (Applied Physiology, Nutrition, and Metabolism, 2014)
Recovery from the demands of daily training is an essential element of a scientifically based periodized program whose twin goals are to maximize training adaptation and enhance performance. Prolonged endurance training sessions induce substantial metabolic perturbations in skeletal muscle, including the depletion of endogenous fuels and damage/disruption to muscle and body proteins. Therefore, increasing nutrient availability (i.e., carbohydrate and protein) in the post-training recovery period is important to replenish substrate stores and facilitate repair and remodelling of skeletal muscle. It is well accepted that protein ingestion following resistance-based exercise increases rates of skeletal muscle protein synthesis and potentiates gains in muscle mass and strength. To date, however, little attention has focused on the ability of dietary protein to enhance skeletal muscle remodelling and stimulate adaptations that promote an endurance phenotype. The purpose of this review is to critically discuss the results of recent studies that have examined the role of dietary protein for the endurance athlete. Our primary aim is to consider the results from contemporary investigations that have advanced our knowledge of how the manipulation of dietary protein (i.e., amount, type, and timing of ingestion) can facilitate muscle remodelling by promoting muscle protein synthesis. We focus on the role of protein in facilitating optimal recovery from, and promoting adaptations to strenuous endurance-based training.